The Distribution Pattern of Higher Education Institutions in Central Java: A Secondary Data Analysis as a Basis for Educational Research - Juni Amanullah; Moh. Yudik Al Faruq (Journal of Education and Teacher Development, 2025)
This study investigates the distribution patterns of higher education institutions across Central Java Province by utilizing available secondary data. Using a descriptive quantitative approach, the research analyzes the spatial distribution of institutions based on administrative regions, ownership status (public or private), and institutional type—namely universities, colleges, polytechnics, academies, and institutes. The findings demonstrate notable regional disparities, with higher education institutions largely concentrated in urban centers such as Semarang and Surakarta. In contrast, several regencies remain underserved, highlighting a pressing imbalance in educational infrastructure. A key observation is the dominance of private higher education institutions, which account for the majority of active providers in the province. Most of these are universities and colleges, pointing to a trend toward certain institutional models. This uneven distribution not only reflects geographical imbalances but also raises questions regarding access, equity, and the long-term development of human capital at the regional level. By offering a data-driven snapshot of institutional presence, this study serves as a foundational resource for policymakers, educators, and researchers. It emphasizes the importance of equitable educational planning and advocates for more inclusive policies that address gaps in higher education access. The research contributes to a broader discourse on regional development and educational equity in Indonesia.